Development and Evaluation of Surface-Functionalized Rifampicin Nanoparticles for Targeted Pulmonary Drug Delivery in Tuberculosis Therapy - Aglawe, Sachin; Athare, Om Ankush; Jadhav, Vijay; Aghade, Karveer; jain, Nitin; jain, Usha; Kawade, Dadasaheb (International Journal of Aquatic Research and Environmental Studies, 2026)
Pulmonary tuberculosis (TB) remains a global health crisis, with conventional rifampicin therapy limited by poor bioavailability, non-specific distribution, dose-related hepatotoxicity, and frequent dosing requirements. This study aimed to develop surface-functionalized rifampicin-loaded polymeric nanoparticles (NPs) to overcome these limitations. Five nanoparticle formulations (F1–F5) were prepared using solvent evaporation with PLGA/Eudragit RS100 polymers, followed by chitosan surface functionalization. Physicochemical characterization revealed uniform spherical particles (176.8–286.4 nm) with excellent stability (zeta potential: −18.2 to −31.5 mV) and high drug entrapment efficiency (68.4–89.7%). In vitro drug release demonstrated sustained, controlled release over 24 hours. Notably, surface-functionalized nanoparticles exhibited 50% enhanced cellular uptake by macrophages (87.6%) compared to non-functionalized formulations (58.4%), confirming superior macrophage targeting efficiency. FTIR spectroscopy confirmed drug-polymer compatibility without chemical degradation. The optimized formulation F5 demonstrated maximum drug loading (22.9%), highest entrapment efficiency (89.7%), smallest particle size (176.8 nm), and most controlled release profile, making it an ideal candidate for pulmonary TB therapy. Surface functionalization with chitosan emerged as a critical strategy for improving therapeutic delivery to the intracellular site of M. tuberculosis infection. These findings suggest that surface-functionalized rifampicin nanoparticles represent a promising innovation to improve therapeutic efficacy, reduce dosing frequency, minimize systemic toxicity, enhance patient compliance, and potentially contribute to overcoming drug resistance in TB management.
Keywords: Rifampicin, nanoparticles, surface functionalization, chitosan, macrophage targeting, pulmonary drug delivery, tuberculosis, PLGA, sustained release, mycobacterium tuberculosis.